To determine which option contains two coefficients and three terms, let's analyze each option:
Option #1: \(2x - 3 = 4 - y\)
Rearranging it gives: \(2x - y - 7 = 0\)
Terms: \(2x\), \(-y\), \(-7\)
Coefficients: \(2\) (for \(x\)), \(-1\) (for \(y\))
Total terms: 3
Total coefficients: 2
Option #2: \(6 + 7y = 5\)
Rearranging gives: \(7y + 1 = 0\)
Terms: \(7y\), \(1\)
Coefficients: \(7\) (for \(y\))
Total terms: 2
Total coefficients: 1
Option #3: \(9x = 1 - 8x\)
Rearranging it gives: \(9x + 8x - 1 = 0\)
Terms: \(9x\), \(8x\), \(-1\)
Coefficients: \(9\) (for \(x\)), \(8\) (for \(x\) again)
Total terms: 3
Total coefficients: 1
Considering all options, Option #1 meets the criteria of having two coefficients and three terms.
Thus, the answer is: Option #1.